2020
DOI: 10.1097/jsm.0000000000000869
|View full text |Cite
|
Sign up to set email alerts
|

Consensus Recommendations on the Prehospital Care of the Injured Athlete With a Suspected Catastrophic Cervical Spine Injury

Abstract: Introduction: Sports participation is among the leading causes of catastrophic cervical spine injury (CSI) in the United States. Appropriate prehospital care for athletes with suspected CSIs should be available at all levels of sport. The goal of this project was to develop a set of best-practice recommendations appropriate for athletic trainers, emergency responders, sports medicine and emergency physicians, and others engaged in caring for athletes with suspected CSIs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Researchers also used a dual-task paradigm combining the MOT task with either a visual search task or an auditory discrimination task and found that the MOT task did not share attentional resources with the visual search task but occupied attentional resources with each other with the auditory discrimination task. It has also been suggested that two tasks that both rely on visual input may cause confounding of visual attentional resources due to visual processing interactions, and to avoid interference between the two visual tasks, this study combined the MOT task and the pitch discrimination task [14]. It was found that the MOT task and the pitch discrimination task performed worse when completed simultaneously than when completed separately, suggesting that multitarget tracking requires attentional engagement.…”
Section: Related Workmentioning
confidence: 92%
“…Researchers also used a dual-task paradigm combining the MOT task with either a visual search task or an auditory discrimination task and found that the MOT task did not share attentional resources with the visual search task but occupied attentional resources with each other with the auditory discrimination task. It has also been suggested that two tasks that both rely on visual input may cause confounding of visual attentional resources due to visual processing interactions, and to avoid interference between the two visual tasks, this study combined the MOT task and the pitch discrimination task [14]. It was found that the MOT task and the pitch discrimination task performed worse when completed simultaneously than when completed separately, suggesting that multitarget tracking requires attentional engagement.…”
Section: Related Workmentioning
confidence: 92%
“…Equipment should be readily available and strategically placed to help manage these injuries, in accordance the EAP. Devices required to remove helmets, shoulder pads, and other protective equipment should be accessible (6).…”
Section: Sport-specific Considerationsmentioning
confidence: 99%
“…The weak point of this technique is that it permits excessive motion in the cervical spine from rotation over the shoulder [1,3]. Current recommendations concerning prehospital care of patients with a suspected catastrophic cervical spine injury emphasize that maintaining cervical spine alignment should be given the highest priority for any transfer technique [4]. The consensus decision advocates an 8-person lift-and-slide technique for supine patients and a log-roll push technique for prone patients.…”
mentioning
confidence: 99%
“…The consensus decision advocates an 8-person lift-and-slide technique for supine patients and a log-roll push technique for prone patients. The consensus decision also advocates that the medical team be proficient in multiple transfer techniques to provide the best on-scene care [4]. Whereas many welltrained rescuers are readily available at sport centers during training and competition, the availability of enough rescuers to perform an 8-person lift technique is unlikely in wilderness accidents.…”
mentioning
confidence: 99%